Psychomotor profile of a child with specific language impairment and Dyslexia - Dias Tânia; Helena Mesquita (Universidade Federal de Santa Maria (UFSM), 2013)
Projecting beyond the ideia of the organic and expressive body and cementing a close relationship between motor skills, cognition and language, the current practices Psychomotricity reach a new conceptual field. In this paper of qualitative nature, it was intended to draw the psychomotor profile of a 8 years old child with Specific Language Impairment (SLI) and Dyslexia, by using the Vitor da Fonseca 's Observation Psychomotor Battery (OPB) and correlate it with the linguistic and cognitive profiles. Through the triangulation of the results obtained in psychomotor, cognitive and language tests, the data in literature was corroborated, which clearly point to the existence of co-morbidity between PEL, Dyslexia and disturbances in the psychomotor's profile, thereby demonstrating a strong correlation between psychomotricity, cognition and language. Therefore, it's urgent, and possible, to sensitize the family, the health and education professionals for the need to a multidisciplinary approach in the areas of psychomotricity and language, both at a prophylactic or rehabilitative level.